Impressions from Samsun Regional Seminar on Public Libraries - A. Yelda Güneyoğlu (Türk Kütüphaneciliği)
Impressions from Samsun Regional Seminar on Public Libraries hosted by Samsun Public Library and held in cooperation with Turkish Librarians' Association, General Directorate of Libraries and Publications, Hacettepe University Department of Information Management and Goethe Institute on March 5-7, 2010 are conveyed by Yelda Güneyoğlu, a sophomore student at the Department of Information Management.